Computing the bound of an Ore polynomial. Applications to factorization. (May 2019) - Gómez-Torrecillas, José; Lobillo, F.J.; Navarro, Gabriel
Abstract: We develop two algorithms for computing a bound of an Ore polynomial over a skew field, under mild conditions. As an application, we state a criterion for deciding whether a bounded Ore polynomial is irreducible, and we discuss a factorization algorithm. The asymptotic time complexity in the degree of the given Ore polynomial is studied.